Treatment of proximal upper limb tremor with botulinum toxin therapy. Issue 6 (20th November 2013) - Kim, Samuel D.; Yiannikas, Con; Mahant, Neil; Vucic, Steve; Fung, Victor S.C.
ABSTRACT Background Proximal‐dominant upper limb tremor is highly disabling, and there is no effective medical therapy. In this study, we evaluated the efficacy of botulinum toxin (BTX) injections for the treatment of proximal tremor. Methods We conducted a retrospective analysis of open‐label treatment with BTX in 19 patients with proximal tremor. The response to therapy was graded into four categories according to self‐reported improvements in tremor and function. Results In total, 63% of patients reported moderate or marked benefit, defined as functional improvements sufficient enough to allow feeding or drinking from a cup; whereas 21% of patients reported mild benefit; and 15% of patients reported no benefit. One patient developed severe weakness of shoulder abduction and withdrew from the treatment; otherwise, the therapy was free of side effects. Conclusions The current findings support the efficacy of BTX therapy in the treatment of proximal upper limb tremor with minimal side effects. © International Parkinson and Movement Disorder Society © 2013 International Parkinson and Movement Disorder Society